Wasp-mimicking soldier flies of the Australian Region: revision of Ampsalis Walker, Elissoma White and Lagenosoma Brauer (Stratiomyidae: Clitellariinae) - Shaun L. Winterton (Zootaxa, 2023)
The genera Lagenosoma Brauer, 1882 (= Peratomastix Enderlein, 1914 syn. n.), Elissoma White, 1916 (= Pycnothorax Kertész, 1923 syn. n.) and Ampsalis Walker, 1859 (Stratiomyidae: Clitellariinae) are revised. Three species of Elissoma are redescribed (i.e., E. australis (Kertész, 1923) comb. n., E. brunnea, Hardy, 1933, and E. lauta White, 1916) and seven species are described as new. Similarly, three species of Lagenosoma are redescribed (i.e., L. dispar Brauer, 1882 (= Peratomastix australis Enderlein, 1914 syn. n.), L. pictum Brauer, 1882 and L. propinquum Brauer, 1882) and seven species are described as new. Ampsalis sensu lato is represented by two species in Indonesia and two species in Madagascar; here the Indonesian species are circumscribed as Ampsalis sensu stricto (i.e., A. geniata Walker, 1859 and A. iterabilis (Walker, 1859)) with two additional species described from northern Australia. Eudmeta Wiedemann, 1830 is diagnosed and a new synonymy identified (i.e., E. marginata (Fabricius, 1805) (= E. coerulemaculata Yang, Wei et Yang, 2010 syn. n.)). A revised key to Clitellariinae genera of the Oriental and Australian regions is presented, as well as keys to species of Ampsalis, Elissoma, Eudmeta and Lagenosoma.